Two CMOS Wilkinson Power Dividers Using High Slow-Wave and Low-Loss Transmission Lines - Chatrpol Pakasiri; Wei-Sen Teng; Sen Wang (Micromachines, 2024)
.
Keywords: Radio Frequency Integrated Circuit Design; Semiconductor materials and devices; Photonic and Optical Devices